Observation of complete energy transfer by orthogonally polarized Raman scattering in a high-birefringence fiber - Hao, Qiang; Liu, Yang; Li, Xuexue; Luo, Peng; Zeng, Heping (Optics letters, 2025)
This study reports the observation of complete orthogonally polarized Raman scattering (OPRS) in a 1.0-km high-birefringence fiber (HBF). An incident pump pulse at 1560 nm with an energy of 2.48 nJ and a duration of less than 100 fs is aligned along the slow axis of the HBF. Initially, the incident pump pulse generates a Raman soliton and experiences soliton self-frequency shift (SSFS) along the slow axis. When the energy of the incident pump pulse reaches 0.74 nJ, the Raman soliton in the slow axis induces and amplifies a new, to the best of our knowledge, spectral component referred to as generated pulse in the fast axis through OPRS. Subsequently, the two orthogonally polarized pulses trap each other through cross-phase modulation, temporally overlap, and copropagate along the fiber until the energy of the Raman soliton in the slow axis is depleted. Finally, the generated pulse in the fast axis autonomously undergoes the SSFS process, extending beyond 1770 nm. Notably, the second OPRS process is observed as the energy of the incident pump pulse reaches 1.55 nJ.